The Effects of Remimazolam versus Propofol on Endovascular Thrombectomy for Acute Ischemic Stroke: Study Protocol for a Randomized Controlled Trial - Fu L; Zhou R; Jiang W; Lan L; Chen X; Cao Y; Xia L; Zhou Y; Han J; Zhou D; Zhang X (Vascular Health and Risk Management)
Lijuan Fu,1,* Rui Zhou,2,* Wencai Jiang,1 Lan Lan,1 Xuemeng Chen,1 Yuansheng Cao,1 Leqiang Xia,1 Yukai Zhou,1 Jia Han,1 Dan Zhou,1 Xianjie Zhang1 1Department of Anesthesiology, Deyang People’s Hospital, Deyang City, Sichuan Province, People’s Republic of China; 2Department of Anesthesiology and Perioperative Medicine, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai City, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xianjie Zhang, Department of Anesthesiology, Deyang People’s Hospital, No. 173, Section 1 of North Taishan Road, Deyang City, Sichuan Province, 618000, People’s Republic of China, Tel +8613981088319, Email zhangxianjie791002@163.comBackground: While general anesthesia has been widely used in endovascular thrombectomy for acute ischemic stroke (AIS), the optimal anesthesia medication for hemodynamic management remains unclear.Purpose: To compare the effects of remimazolam and propofol on endovascular thrombectomy for AIS.Methods: This study is a single-center, double-blind and randomized controlled trial. Eligible patients will be randomly allocated into the remimazolam group and propofol group. Remimazolam and propofol will be administered to induce and maintain anesthesia respectively. The primary outcome is the incidence of intraoperative hypotension. The secondary outcomes include frequency of hypotension, the largest difference value of mean arterial pressure (MAP), dosage of vasopressors, extubation time, operation time, modified thrombolysis in cerebral infarction (mTICI) level, National Institutes of Health Stroke Scale (NIHSS) score and modified Rankin scale (mRS) score.Conclusion: This study evaluates the influences of remimazolam versus propofol on endovascular therapy for AIS patients. Results of this study are expected to provide more evidence of the choice of anesthetics in this kind of operation.Trial Registration: This study has been registered at the Chinese Clinical Trial Registry (ChiCTR2300076880).Keywords: remimazolam, acute ischemic stroke, endovascular thrombectomy, intraoperative hypotension, outcomes